Deep learning with R cookbook : over 45 unique recipes to delve into neural network techniques using R 3.5x - Gupta, Swarna; Ansari, Rehan Ali; Sarkar, Dipayan (Packt Publishing, 2020)
This book will help you get through the problems that you face during the execution of different tasks and understand hacks in deep learning. With unique recipes, you will implement various deep learning architectures using R 3.5.x. You will cover complex algorithms to perform tasks such as reinforcement learning, GANs, advanced neural ...